Pixton Digital Comic Media in PPKN Lessons to Improve the Character Profile of Pancasila Students - Sari, Pratiwi Kartika; Ninggar Renata Putri (LPPM Undiksha, 2025)
The limited use of digital media in fostering the Pancasila Student Profile character has become a concern. This study aims to develop Pixton-based digital comic media through Civics Education (PPKn) to enhance students' Pancasila Student Profile character. The digital comic in this study was created using a web-based program called Pixton. This research used the Research and Development (R&D) method, applying the Borg and Gall model. Data collection techniques included observation, documentation, questionnaires, and tests. Validation subjects consisted of three experts: a language expert, a content expert, and a media expert. The trial subjects were fifth-grade students in an elementary school. The feasibility of the media was indicated by validation results: 87.08% from the media expert, 96.66% from the content expert, and 84.44% from the language expert. Based on the analysis of pre-test and post-test data using a paired sample t-test, a significance value of 0.000 < 0.05 was obtained, indicating an improvement in students' learning outcomes after using the product. The conclusion of the study is that the development of digital media is feasible and effective for enhancing students’ Pancasila Student Profile character and suitable for classroom implementation. The implication of the research is that the product facilitates student learning, helps improve learning outcomes related to the Pancasila Student Profile character, and supports teachers in delivering information effectively, thus achieving learning objectives.